Proteus mirabilis MR/P fimbriae: molecular cloning, expression, and nucleotide sequence of the major fimbrial subunit gene. - Bahrani, F K (1993)
Proteus mirabilis, a cause of serious urinary tract infection and acute pyelonephritis, produces several putative virulence determinants, among them, fimbriae. Principally, two fimbrial types are produced by this species: mannose-resistant/Proteus-like (MR/P) fimbriae and mannose-resistant/Klebsiella-like (MR/K) fimbriae. To isolate MR/P fimbrial gene sequences, a P. mirabilis cosmid library was screened by immunoblotting and by hybridization with an oligonucleotide probe based on the N-terminal amino acid sequence of the isolated fimbrial polypeptide, ADQGHGTVKFVGSIIDAPCS. One clone, pMRP101, reacted strongly with a monoclonal antibody specific for MR/P fimbriae and with the DNA probe. This clone hemagglutinated both tannic acid-treated and untreated chicken erythrocytes with or without 50 mM D-mannose and was shown to be fimbriated by transmission electron microscopy. A 525-bp open reading frame, designated mrpA, predicted a 175-amino-acid polypeptide including a 23-amino-acid hydrophobic leader peptide. The unprocessed and processed polypeptides are predicted to be 17,909 and 15,689 Da, respectively. The N-terminal amino acid sequence of the processed fimbrial subunit exactly matched amino acid residues 24 to 43 predicted by the mrpA nucleotide sequence. The MrpA polypeptide shares 57% amino acid sequence identity with SmfA, the major fimbrial subunit of Serratia marcescens mannose-resistant fimbriae.